Artisanal Mining Practices: A Study Of Selected Counties In Kenya - Arasa, Robert; Achuora, John; Okello, Cornelius (Researchgate, 2020)
Artisanal miners extract natural resources (mostly gold, copper, sand and quarry) from easily accessible deposits using the only very basic tools. It is undertaken in different forms - underground mining (below the surface), open surface (pit) mining, placer mining (by divers in rivers) and solution mining (drilled boreholes). In Kenya, these include mining of gold, gemstones, copper, quarry, sand among other minerals. In Kenya, these practices are commonly notable in Kakamega, Migori, Homa Bay, Kwale, Machakos, Kitui, Kajiado and Kisii Counties. This research project set out to examine artisanal mining practices within the selected counties in Kenya. A participatory survey approach was pursued to aid gathering of relevant and appropriate data. The study was confined to the five selected counties (Migori, Kakamega, Kisii, Kajiado and Kitui) where artisanal mining (ASM) activities take place. Respondents were drawn from relevant county government departments, miners and local leaders. Primary data was gathered through FGDs, KII and use of structured questionnaires. Descriptive technique was employed to analyze the collected data and information. The study findings revealed that 38.1 percent and 31.2 percent of the respondents practiced underground mining and open surface mining respectively. Less than one percent of the respondents practiced solution mining. Findings revealed that ASM provides a source of income to those involved. Many of those engaged in ASM are mainly the poor struggling to earn a living to support their basic needs, though the earnings raised still stand far from being adequate. The study revealed that there are numerous negative effects arising from ASM ranging from environmental degradation, health risks, landscape interference, accidents, interfering with quality of soil, water siltation among others. It was noted that most of the miners lack adequate knowledge and skills on safe and best mining practices. Further it was noted that the current regulatory framework for the sub-sector is either lacking or ineffective. The study recommendations include; fast-tracking on formalization of ASM, reviewing mining regulatory framework, encourages miners to form cooperatives, strengthen monitoring on adherence to mining regulations and guidelines, capacity building for miners in terms of knowledge and mining skills, ASM activities to be given more attention at county and national governments.
Keywords: Artisanal mining; underground mining; open surface; placer mining; solution mining